Improved properties of Pt-HfO2 gate insulator-ZnO semiconductor thin film structure by annealing of ZnO layer - Na, Kwang Duk; Kim, Jeong Hwan; Park, Tae Joo; Song, Jaewon; Hwang, Cheol Seong; Choi, Jung-Hae (ELSEVIER SCIENCE SA, 2010)
Metal-insulator-semiconductor capacitors were fabricated with sputtered ZnO and atomic layer deposited HfO2 as the semiconductor and gate dielectric layers, respectively. From the capacitance-voltage measurements, it was confirmed that pre-deposition annealing of the sputtered ZnO layer at 300 degrees C in air greatly decreased the interfacial trap density (similar to 2 x 10(12) cm(-2) eV(-1)), X-ray photoelectron spectroscopy showed a decrease in the OH bonds adsorbed on the ZnO surface after pre-deposition annealing, which improved the interface property. A very small capacitance equivalent thickness of 1.3 nm was achieved, which decreased the operation voltage (<5V) of the device significantly. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: OXIDE; TRANSISTORS; DEPOSITION; MOBILITY